Implications of Parenting Patterns in the Development of Early Childhood Social Attitudes - Rahimah Rahimah; Ismail Koto (International Journal Reglement & Society (IJRS), 2022)
The family is the first and foremost educational environment. The family is the most important part of human life, which consists of a father, mother and child. While children are individuals who are developing where they really need special attention from their parents. The research method used is normative juridical. The results showed that in authoritarian parenting patterns that tend to punish children, authoritarian parents tend to give implications that make children anti-social, kill children's curiosity, experience restraint of creativity, limitation of movement space, lack of warmth in children, dialogical processes does not develop, there is only monologue. Parents do not allow children to think critically. It is possible that this parenting pattern is a hereditary parenting pattern so that children are likely to imitate this parenting pattern for the next generation. Furthermore, permissive parenting, the implication of this parenting pattern is that children grow into uncontrolled children, children can be very spoiled by their parents and result in children not being independent, parents obeying children excessively and do not provide clear and consistent rules, parents always succumb to children, parents shape children dependence on it, children are less able to control emotions, children's maturity tends to be slow, as a result children are less independent and confident